Discrepancy Evaluation of A CBSA-Based Iqra’ Program at LPQ AMM Yogyakarta - Wafiq, Ainun; Suwadi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
Qur’anic reading programs require not only appropriate instructional methods but also clear implementation standards, consistent teacher decisions, and adequate evidence of student progress. Previous studies on the Iqra’ method have largely focused on instructional implementation and reading outcomes, At the same time, limited attention has been given to whether program implementation conforms to explicit institutional standards across different stages of evaluation. This study employed an evaluative qualitative case-study design at LPQ AMM Yogyakarta using Provus’s Discrepancy Evaluation Model as the primary analytical framework. Fifteen informants participated, comprising one program coordinator, seven instructional personnel consisting of supervisors and teachers, and seven students. Data were collected through semi-structured interviews, classroom observations, and document analysis and were compared across the design, installation, process, and product stages. The findings indicate partial conformity between program expectations and implementation. At the design stage, the program had a clear graduation target but lacked measurable indicators for CBSA, correction, repetition, and promotion. At the installation stage, training, syahadah certification, and supervision were available, although teacher calibration remained incomplete. At the process stage, guided self-correction and direct correction were both used without a uniform decision rule. At the product stage, progress books supported monitoring and promotion decisions but did not provide sufficient evidence to demonstrate improvement in Qur’anic reading ability or a causal effect of CBSA. These findings suggest that program improvement should prioritise measurable CBSA indicators, shared correction protocols, teacher calibration, and more detailed progress records.